ANALISIS HUBUNGAN ANTARA PERTUMBUHAN EKONOMI DAERAH, BELANJA PEMBANGUNAN DAERAH DAN PENDAPATAN ASLI DAERAH KABUPATEN ACEH UTARA - Naz’aina ' (Program Studi Pendidikan Ekonomi Universitas Riau, 2013)
Regional fiscal desentralisation is an opportunity for regions to manage and controllocal community interests based on the community’s aspiration. In addition, localgovernment possesses wider authority to run owned resources efficiently. Theresearch’s objective is ti find out how development expenditure affects regionaleconomic growth and revenue and how to regional economic growth affects regionalrevenue. The research used time series data from 2000 – 2010. Data is processedand analysed used Path Analysis. Result of the research shows that KabupatenAceh Utara regional development expenditure has positive and significant aspectstoward regional revenue of Kabupaten Aceh Utara by standardized betadevelopment expenditure s 0,60 and significant at 0,,028. Meanwhile, partiallyrregional development expenditure of Kabupaten Aceh Utara has positive andsignificant effect toward regional revenue of Kabupaten Aceh Utara. For economicgrowth variable partially has negative and significant effect toward regionalrevenue.In order to maximize economic growth in Kabupaten Aceh Utara, governmentisexpected to revive old industries such as PT. Arun, Exxon Mobil, PT. AAF, PT.PIM and PT. KKA.Keywords: Fiscal desentralisation, economic growth, regional revenue